1991
DOI: 10.1113/jphysiol.1991.sp018523
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fluid secretion from isolated rat pancreatic ducts stimulated with secretin and bombesin.

Abstract: SUMMARY1. Micropuncture techniques were used to study the cellular mechanisms of fluid secretion by interlobular ducts isolated from the pancreas of copper-deficient rats.2. Perifusing ducts with a calcium-free buffer containing 5 mM-EGTA reduced the volume of fluid secreted in the presence of 10 nM-bombesin by 62 %, whereas fluid secretion measured in the presence of 10 nM-secretin was reduced by only 26 %. 4. SITS (4-acetamido-4'-isothiocyanatostilbene-2,2'-disulphonic acid; mM), reduced fluid secretion meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 36 publications
3
41
1
2
Order By: Relevance
“…Previously, we have shown that secretin and bombesin are potent stimulants of fluid secretion from isolated pancreatic ducts Ashton et al 1991), whereas substance P acts as an inhibitor ). We therefore tested the effect of these substances on duct cell [Ca2+]i and found that neither secretin (10 nm, six ducts), bombesin (10 nm to 1 /UM, ten ducts) nor substance P (0-1-1 fM, nine ducts) had any effect on this parameter, although the same ducts responded to ACh.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we have shown that secretin and bombesin are potent stimulants of fluid secretion from isolated pancreatic ducts Ashton et al 1991), whereas substance P acts as an inhibitor ). We therefore tested the effect of these substances on duct cell [Ca2+]i and found that neither secretin (10 nm, six ducts), bombesin (10 nm to 1 /UM, ten ducts) nor substance P (0-1-1 fM, nine ducts) had any effect on this parameter, although the same ducts responded to ACh.…”
Section: Resultsmentioning
confidence: 99%
“…If, as we believe, most of this chloride-rich fluid originates from the ducts (see above), then the ductal epithelium must be capable of switching from HCO3-to Cl-secretion depending on the type of stimulant to which it has been exposed. Previously, we have speculated that this switch could be achieved by moving one of the transport elements located in the duct cell (a Cl--HCO3-exchanger) from the apical to the basolateral plasma membrane (Ashton et al 1991). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Latter studies isolated ducts by microdissection from pancreas of rats, guinea pigs, and mice partially digested with collagenase. Secretin has been shown to stimulate bicarbonate fluid in the isolated duct fragments by microperfusion and by letting the ends of the ducts seal in culture after which the volume increase can be monitored by video microscopy and the ion content sampled by micropuncture (3,34,46). Guinea pig ducts have been especially useful because they secrete a high concentration of bicarbonate similar to humans while rats and mice secrete lower amounts (100).…”
Section: In Vitro Studies Of Secretin Action On Pancreatic Ductsmentioning
confidence: 99%